Dll1+ quiescent tumor stem cells drive chemoresistance in breast cancer through NF-κB survival pathway - Sushil Kumar (Nature Portfolio, 2021)
Although activated Notch receptors have been associated with chemoresistance in cancer, the role of specific Notch ligands remain elusive. Here, the authors show that in breast cells the Notch ligand DLL1 is expressed in cells with a cancer stem cell phenotype and promote doxorubicin resistance in part through NF-kB, as well as metastasis.